2019
DOI: 10.5847/wjem.j.1920-8642.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of endotracheal tube placement using disposable fiberoptic bronchoscopy in the emergent setting

Abstract: BACKGROUND: Patients intubated in the prehospital setting require quick and definitive confi rmation of endotracheal (ET) tube placement upon arrival to the emergency department (ED). Direct and adjunct strategies exist, but each has limitations and there is no defi nitive gold standard. The utility of bronchoscopy in ED intubation has been studied, but scant literature exists on its use for ET tube confi rmation. This study aims to assess effectiveness, ease and speed with which ET tube placement can be confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Disposable fiberoptic bronchoscopes have been previously described to be used in emergent settings to confirm the position of endotracheal tubes. [ 8 ] Bronchoscopes can be threaded through previously placed endotracheal tubes and have been proven to be accurate, quick, and relatively easy to do. Inspired by use of bronchoscopes, the senior anesthetist who performed the intubation mentioned in the cases described, chose to disassemble the digital head to thread the endotracheal tube after confirming the placement of the bronchoscope tip between the vocal cords.…”
Section: Discussionmentioning
confidence: 99%
“…Disposable fiberoptic bronchoscopes have been previously described to be used in emergent settings to confirm the position of endotracheal tubes. [ 8 ] Bronchoscopes can be threaded through previously placed endotracheal tubes and have been proven to be accurate, quick, and relatively easy to do. Inspired by use of bronchoscopes, the senior anesthetist who performed the intubation mentioned in the cases described, chose to disassemble the digital head to thread the endotracheal tube after confirming the placement of the bronchoscope tip between the vocal cords.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound imaging for ETT placement confirmation or endoscopy has been reported; however, their limited availability, requirement for user experience, labor intensiveness, and cost hinder their use in clinical settings. Like CXR, these monitoring methods may only provide a single moment-in-time assessment of placement rather than a continuous assessment of tube position 4 , 19 , 21 , 22 . Currently, SonarMed (formally named AirWave) is an FDA-approved device for real-time ETT airway monitoring for neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Like CXR, these monitoring methods may only provide a single moment-in-time assessment of placement rather than a continuous assessment of tube position. 4 , 19 , 21 , 22 Currently, SonarMed (formally named AirWave) is an FDA-approved device for real-time ETT airway monitoring for neonates. However, an earlier pilot study showed notable discrepancies in the results compared to those obtained with CXR.…”
Section: Introductionmentioning
confidence: 99%
“…Fiberoptic nasopharyngoscopy can serve as a lifesaving airway skill. [10][11][12][13][14][15][16] Allowing visualization of laryngeal anatomy provides valuable diagnostic information in angioedema, airway obstruction, and many other head and neck airway emergencies. While intubations are frequently encountered in practice, fiberoptic nasopharyngoscopy is far less often used but extremely useful, making it ideal for simulation-based training.…”
Section: Introductionmentioning
confidence: 99%